Delayed breast cancer presentation: hospital data should inform proactive primary care - Tessa S. Marcus; Samy Lunda; Leticia Fernandez (AOSIS, 2013)
Background: Breast (and cervical) cancer affects a growing proportion of women in South Africa. Although treatable, where health literacy is low, women typically seek medical attention only when their condition is at an advanced stage and difficult to contain. Objectives: To understand the sociodemographic characteristics of women who present with advanced breast cancer in order to intervene proactively in primary care. Method: A retrospective analysis of women with advanced breast cancer (Stage IIb and higher) at a Level 2 regional hospital in South Africa (2007-2010). Results: The average age amongst the 103 women enrolled in this study was 59. One-third of the women had secondary education, 35% were unemployed and two-thirds were notmarried. Nearly 11% (n = 11) of the women had previously had cancer. Lumps (n = 87) werethe most common reason for seeking healthcare and were, together with axillary lymphnode abnormalities (84.5% and 19.4% respectively), the most common clinical symptoms. Symptoms were noticed by 52% (n = 54) of the women more than six months prior to their first consultation. A personal history of cancer increased threefold the odds of presenting within three months. Middle-aged women were twice as likely as those < 45 and > 65 to report within three to six months. Secondary education increased the odds of presenting within three to six months by 56%. Employment and marital status were not significant. Conclusion: The women most at risk for delayed detection and treatment were those without a history of breast cancer, aged < 45 and > 65, with low education. They can best be reached through low-cost community orientated primary care that proactively provides health education and promotes self- and clinical examination at the individual, family, clinic and general practitioner level.